2017
DOI: 10.1136/bjsports-2017-097492
|View full text |Cite
|
Sign up to set email alerts
|

The Child Sport Concussion Assessment Tool 5th Edition (Child SCAT5): Background and rationale

Abstract: This article presents the Child Sport Concussion Assessment Tool 5th Edition (Child SCAT5). The Sport Concussion Assessment Tool was introduced in 2004, following the 2nd International Conference on Concussion in Sport in Prague, Czech Republic. Following the 4th International Consensus Conference, held in Zurich, Switzerland, in 2012, the SCAT 3rd edition (Child SCAT3) was developed for children aged between 5 and12 years. Research to date was reviewed and synthesised for the 5th International Consensus Confe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 14 publications
0
120
0
1
Order By: Relevance
“…The SCAT5 systematic review14 concluded that studies employing the SCAT (all forms) or its components generally had a low to moderate levels of bias and were generalisable to the larger population, although variability was noted in methodologies, risk of bias, quality of evidence and presentation of data. Overall, the graded symptom checklist, SAC and BESS/mBESS were found to be most useful immediately postinjury in differentiating concussed from non-concussed athletes when using either intraindividual or normative baseline/postinjury comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SCAT5 systematic review14 concluded that studies employing the SCAT (all forms) or its components generally had a low to moderate levels of bias and were generalisable to the larger population, although variability was noted in methodologies, risk of bias, quality of evidence and presentation of data. Overall, the graded symptom checklist, SAC and BESS/mBESS were found to be most useful immediately postinjury in differentiating concussed from non-concussed athletes when using either intraindividual or normative baseline/postinjury comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…The SCAT5 systematic review14 consisted of five different but inter-related searches covering: (1) adult SCAT; (2) child SCAT; (3) sideline assessment; (4) video surveillance/observable signs of concussion and (5) oculomotor assessment. The present paper will only focus on the SCAT5 (for athletes aged over 12 years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCAT541 and the Child SCAT542 are the evaluation tools recommended by the Concussion in Sport Group (CISG) for assessing a suspected concussion. These tests offer a standardised approach to sideline evaluation which incorporates multiple domains of function and are widely available at no cost.…”
Section: Diagnosis Of Concussionmentioning
confidence: 99%
“…The SCAT has been revised several times with the most recent in 2016, the SCAT5 for adults2 and the Child SCAT5 for children under 13 3. All versions of the SCAT were designed for use by healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%